The Administration of Cinnamon (Cinnamomum burmannii) Extract Reduced Weight and Abdominal Visceral Fat in Obese Male Wistar Strain Rats (Rattus Norvegicus) With Moderate Intensity Physical Exercise - Dian Andrieany Husodo; Alex Pangkahila; IGM. Aman (Fakultas Kedokteran Universitas Udayana, 2021)
Introduction: Obesity increases the risk of many degenerative disease. Abdominal fat is a sign that someone has great risk for metabolic syndrome. Moderate physical exercise is suggested to reduce weight and body fat percentage. Cinnamon (Cinnamomum burmannii) extract can reduce weight by the lipolysis activity in visceral adipose tissue and supress the appetite. This research aimed to prove that administration of cinnamon extract reduced weight and abdominal visceral fat in obese male wistar strain ratswith moderate intensity physical exercise. Methods: This research was a true experimental with post-test only control group design. The subjects were 36 male albino rats (Rattus norvegicus), Wistar strain, healthy, 4-5 months age, and obese (body weight of > 250 g), which divided into two groups (n= 18). The positive control group (P1) was treated with placebo (2 ml aquadest), standard food, and moderate physical exercise. The experimental group (P2) was treated with 1000 mg/kg BW/day cinnamon extract standard food, and moderate physical exercise. After 2 weeks of treatment, body weight and abdominal visceral fat mass were measured. Results: The average body weight of the P2 group was significantly lower than the P1 group (271.9±5.48 and 284.7±5.05 g respectively, p<0.001). The median abdominal visceral fat mass in the P1 group was 9.0 g, whereas the P2 group was 7.9 g (p<0.001). The median remaining food in the P1 group was 3.43 g, whereas the P2 group was 10.07 g (p<0.001). Conclusion: This study indicated that administration of cinnamon extract reduced weight and abdominal visceral fat in obese male wistar strain ratswith moderate intensity physical exercise.